Current and Emerging mHealth Technologies Adoption, Implementation, and Use (Springer International Publishing, 2018)
The promise and prospects for mobile technologies in healthcare service delivery-particularly as experienced by patients and other users-are the focus of this forward-looking volume. Its detailed sociotechnical perspective takes in factors influencing patient and provider adoption of technological advances, in addition to the well-known cost and accessibility advantages. Enlightening reports show mobile health technologies in multiple contexts as an impetus for behavioral change, a means of monitoring health changes, a growing trend in service delivery, and an emerging health frontier worldwide. Together, these chapters point to the continued expansion-and global reach-of mobile technology in the next stage of healthcare services. Included in the coverage: Behavior change techniques used in mobile applications targeting physical activity: a systematic review Mobile health integration in pregnancy Unintended users, uses, and consequences of mobile weight loss apps: using eating disorders as a case study Intention vs. perception: understanding the differences in physicians' attitudes towards mobile health applications HealthGuide: a personalized mobile patient guidance system Adoption of sensors in mobile health Current and Emerging mHealth Technologies is salient reading for researchers interested in mobile health development and implementation as well as technology adoption, and mobile health system developers and managers who are interested in the implications of mobile health use by patients and/or healthcare professionals. It can also be used for courses in technology adoption and health technologies. .